The architecture of the GhD7 promoter reveals the roles of GhD7 in growth, development and the abiotic stress response in rice. (October 2019) - Herath, Venura
Graphical abstract: Highlights: The GhD7 promoter consists of 456 transcription factor binding sites. Identified binding sites belong to 25 transcription factor families. The GhD7 promoter consists of a CPG island and a DHS site. Variations in transcription factor binding sites were found among rice accessions. The GhD7 promoter architecture supports its role in development and stress response. Abstract: Grain number, plant height and heading date 7 ( GhD7 ) is considered to be one of the key yield-related genes in the production of high-yielding and climate-ready super rice varieties. GhD7 delays the plant's flowering under long-day conditions, which ultimately results in increased yield. Recent findings indicate that GhD7 also plays a major role in the abiotic stress response; however, the fine regulatory mechanisms controlling Ghd7 expression have yet to be uncovered. This study was carried out to explore the transcription factor binding site (TFBS) architecture of the GhD7 promoter to identify the regulatory dynamics of GhD7 transcription. The promoter sequence (-2000 to +200 base pairs from the transcription start site) was retrieved from the PlantPAN 2.0 database. Ab initio promoter analysis, DNase I hypersensitive site (DHS) analysis, and methylation analysis were carried out to identify TFBSs. The TFBS diversity among rice varieties was also assessed. In addition to the previously identified 8 cis -elements, 448 novel cis -elements were identified in the GhD7 promoter that provide binding sites for 25 transcription factor families. Furthermore, a DNase I hypersensitive site and a CpG island were also identified. The identified transcription factor families include key transcription factors involved in both development and abiotic stress responses, revealing the regulatory dynamics of GhD7 . Comparative analysis of multiple GhD7 promoters identified 31 single-nucleotide polymorphisms that result in TFBS variations among rice accessions. These variations are mostly found in relation to flowering and abiotic stress responsive TFBSs on the promoter. This study supports the model that GhD7 acts as a central regulator of rice growth, development, and the abiotic stress response.